Risk Factors of Vesicovaginalis Fistule in Obstetric and Gynecologic Division of Dr. Mohammad Hoesin General Hospital in 2018-2020 - Nabila Istighfarin; Hadrians Kesuma Putra; Eka Handayani Oktharina; Ratih Krisna; Septi Purnamasari (HM Publisher, 2022)
Background. A vesicovaginal fistula (FVV) is a direct pathological connection between the bladder and vagina resulting in uncontrolled leakage of urine into the vagina from the bladder. Based on the cause, fistulas are divided into two, namely obstetric fistula and gynecological fistula. The risk factors that influence the occurrence of FFV consist of obstetric risk factors (age, parity, delivery method, duration of delivery, birth weight) and gynecological risk factors (history of gynecological surgery, history of pelvic radiotherapy, history of gynecologic malignancy). The purpose of this study was to determine the relationship between risk factors and the incidence of vesicovaginal fistula. Methods. This research is an observational-analytic study with a cross-sectional method. The number of samples obtained was 74 patients who met the inclusion criteria using secondary data from medical records. Analysis of the data used is the chi-square test. Results. There were 37 people who experienced vesicovaginal fistula. Where there were 9 patients with obstetric vesicovaginal fistula (24.3%) and 28 people (75.7%). From the Chi-Square test analysis, there was a significant relationship between delivery method (p=0.029), birth weight (p=0.029), history of gynecological surgery (p=0.038), history of pelvic radiotherapy (p=0.016), history of gynecological malignancy (p=0.016). =0.010). Meanwhile, there was no significant relationship between age (p=0,347), parity (p=1,000), and duration of labor (p=0,082). Conclusion. There was a significant relationship between the delivery method, birth weight, history of gynecological surgery, history of pelvic radiotherapy, history of gynecological malignancy. There was no significant relationship between age, parity, and duration of vaginal delivery.